PENINGKATAN KADAR LEPTIN DENGAN PUFA (Polyunsaturated Fatty Acid) MELALUI AKTIVASI PEROXISOME PROLIFERATOR-ACTIVATED RECEPTOR gamma (PPARγ) PADA KULTUR PREADIPOSIT KELINCI - Indra, Muhammad Rasjad (Jurnal Kedokteran Brawijaya, 2005)
ABSTRACT For the past three decades, PUFA has been recognized as importnant energy sources and cell membrane component. PUFA also plays key roles in many cellular events such as gene regulation and leptin activation. The role of this fatty acid is still unknown especially in vitro. The purpose of this research was to examine the effect of PUFA of the corn oil in increasing leptin concentration by PPARγ activation. Preadipocyte culture from rabbit was incubated by PUFA of corn oil. PUFA have been given on doses 0, 4, 8 and 16 µM. PPARγ protein and leptin levels were analyzed by ELISA. PPARγ expression  was  analyzed  by  immunocytochemistry.  The research  result  showed  that  every  treatment  has  increased PPARγ levels inconsistently. PPARγ concentration increased significantly on 4 µM PUFA treatment compared to control, 8 and 16 µM PUFA of corn oil. But there were no significant difference between control and 8 µM PUFA treatments. Leptin levels increased significantly between administration on 4 µM PUFA and 16 µM PUFA of corn oil administration. Leptin levels was not significantly different between control and 8 µM PUFA. There was also strong correlation between PPARγ expression and leptin levels. PUFA of corn oil increases leptin levels through PPARγ activation. Key words: PUFA, preadipocyte, leptin, PPARγ